Heterogeneity of molecular sensitization profiles in grass pollen allergy – implications for immunotherapy?. Issue 5 (May 2014) - Darsow, U.; Brockow, K.; Pfab, F.; Jakob, T.; Petersson, C. J.; Borres, M. P.; Ring, J.; Behrendt, H.; Huss‐Marp, J.
Summary Background Data on molecular allergy diagnostics in adults with grass pollen allergy with regard to conjunctival and nasal provocation test outcome and specific immunotherapy are lacking to date. Objective To assess whether molecular allergy diagnostics for grass pollen allergens could help with predicting provocation test outcomes and serve as a basis for future component‐resolved specific immunotherapy. Methods Sera of 101 adults with grass pollen allergy was analysed for IgE against timothy grass pollen (Phleum pratense), rPhl p 1, rPhl p 2, nPhl p 4, rPhl p 5b, rPhl p 6, rPhl p 7, rPhl p 11 and rPhl p12 and correlated with the individuals' outcome in the nasal and conjunctival provocation tests and investigated in regard to a potential component‐resolved specific immunotherapy. Results An increasing number of sensitizations to timothy grass allergens was correlated to a positive reaction in the conjunctival (4.9 vs. 3.6, P = 0.003) and nasal provocation tests (4.5 vs. 2.2, P = 0.0175). In molecular sensitization profiles, a substantial heterogeneity was detected, with none of the patients exactly matching the allergen composition of a previously published component‐resolved specific immunotherapy containing Phl p 1, Phl p 2, Phl p 5a/b and Phl p 6. The results indicate that in 95% of the patients, a proportion of 50% of timothy‐IgE would be targeted with such a specific immunotherapy, while in 50% and 10% of patients, 80% and 90% of timothy‐IgE would be targeted, respectively. Conclusion and Clinical Relevance Molecular allergy diagnostics is a prerequisite for future component‐resolved specific immunotherapy due to the high heterogeneity of sensitization profiles. However, of current clinical relevance is the observed correlation between the number of sensitizations and provocation test outcome.